1975
DOI: 10.1063/1.431382
|View full text |Cite
|
Sign up to set email alerts
|

Generalization of Slater’s transition state concept

Abstract: We present a generalization of the transition state technique introduced by Slater for the calculation of many-electron relaxation effects accompanying electronic excitations in molecules and molecular simulations of solids. By making use of ground state information (which is generally available but not used in the Slater formulation) and transition states which are computationally cheaper (due to being closer to the ground state), the generalization permits the evaluation of excitation energies to be improved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(80 citation statements)
references
References 13 publications
2
78
0
Order By: Relevance
“…As stated in the previous work, 4 in the generalized transition-states (GTS) method, Williams et al 10 proposed the extension of Slater's transition-state idea 11 and approximated the endothermicity…”
Section: Cebes Of Cls Due To the Slater's Transition State Using Dft mentioning
confidence: 99%
“…As stated in the previous work, 4 in the generalized transition-states (GTS) method, Williams et al 10 proposed the extension of Slater's transition-state idea 11 and approximated the endothermicity…”
Section: Cebes Of Cls Due To the Slater's Transition State Using Dft mentioning
confidence: 99%
“…Ifwe define the first derivative (F(x)=dE(x)/dx), in the generalized transition-state (GTS) method, Williams et al 31 propposed the use of…”
Section: Cebes Of Cls Due To Slater's Concept Of the Transitionstate mentioning
confidence: 99%
“…The method employs an unrestricted generalized transition-state (uGTS) model. 28 Pulfer et al have confirmed the reliability of the method with a total of seventy-six cases. 29 More recently, a more reliable method, called ∆E KS (PW86-PW91)/cc-pCVTZ, was found by Cavigliasso and Chong.…”
Section: Introductionmentioning
confidence: 71%